Molecular characterization of the genome-wide BOR transporter family and their responses to boron conditions in common wheat (Triticum aestivum L.) - Wang, Yuquan; Niu, Zhipeng; Hu, Xigui; Wu, Xiaojun; Yang, Zijun; Hao, Chenyan; Zhou, Mengxue; Yang, Shumin; Dong, Na; Liu, Mingjiu; Ru, Zhengang (Frontiers in Plant Science, 2022)
Boron (B) deficiency is an agricultural problem that causes significant yield losses in many countries. B transporters (BORs) are responsible for B uptake and distribution and play important roles in yield formation. A comprehensive analysis of the BOR family members in common wheat is still lacking. In the present study, to clarify the molecular characterization and response to B status, genome-wide TaBOR genes and expression patterns were investigated. Fourteen TaBOR genes were identified in common wheat by a homology search. The corresponding phylogenetic tree indicated that 14 TaBOR genes were separately classified into subfamilies of TaBOR1, TaBOR3, and TaBOR4. All TaBOR genes had 12–14 extrons and 11–13 introns. Most TaBOR proteins contained 10 conserved motifs, and motifs 1, 2, 3, 4, and 6 constituted the conserved bicarbonate (HCO3–) domain. Fourteen TaBOR genes were mapped on 13 chromosomes mainly distributed in the first, third, fifth, and seventh homologous groups. The promoters of TaBOR genes consisted of phytohormones, light responses, and stress-related cis-elements. GO analysis indicated that TaBOR genes were enriched in terms of transmembrane transport and ion homeostasis. TaBOR genes showed diverse expression profiles in different tissues. The members of the TaBOR1 subfamily showed high expression in grains, leaves, roots, stems, and spikes, but members of the TaBOR4 subfamily were highly expressed only in spikes and grains. RT–qPCR indicated that TaBOR1-5A, TaBOR1-5B, and TaBOR1-5D were induced by low B concentrations and had much higher expression in roots than in shoots. TaBOR3-3A, TaBOR3-3B, TaBOR3-3D, TaBOR4-1A, TaBOR4-1B, TaBOR4-1D, and TaBOR3-4B were induced by low and high B concentrations and had high expression in roots and shoots. TaBOR3-4D and TaBOR3-7B were upregulated by low and high B concentrations, respectively, but had expression only in roots. Our results provide basic information on the TaBOR family, which is beneficial for elucidating the functions of TaBOR genes to overcome the problem of B deficiency.